Brief report: Factor structure of parenting behaviour in early adolescence. (19th September 2016) - Spithoven, Annette W.M.; Bijttebier, Patricia; Van Leeuwen, Karla; Goossens, Luc
ABSTRACT: Researchers have traditionally relied on a tripartite model of parenting behaviour, consisting of the dimensions parental support, psychological control, and behavioural control. However, some scholars have argued to distinguish two dimensions of behavioural control, namely reactive control and proactive control. In line with earlier work, the current study found empirical evidence for these distinct behavioural control dimensions. In addition, the study showed that the four parenting dimensions of parental support, psychological control, reactive control, and proactive control were differentially related to peer‐related loneliness as well as parent‐related loneliness. Thereby, the current study does not only provide empirical evidence for the distinction between various parenting dimensions, but also shows the utility of this differentiation.